"Selling Their Jobs?" Thatcherism, Voluntary Redundancy and Worker Resocialisation. (1st May 2022) - Taylor, Greig; McDonald, Matthew
Abstract : The election of Margaret Thatcher's government in 1979 is widely regarded as a watershed in British history, credited with transforming the country's socioeconomic traditions, as well as helping to inspire a global turn towards neoliberal political economy. Thatcher's project sought not only to promote free market economics, but also propel its accompanying underpinning ideological tenets, such as individualism, competition, enterprise, and consumerism, to primacy in societal discourse. The subjugation of trade union influence was also a fundamental component of the emerging program, and the prevailing narrative is that this was achieved through microeconomic and legislative reform. However, often underplayed is how voluntary severance schemes were used to undermine notions of collectivism, forcing workers to reassess preconceptions regarding the nature of employment and unionism. This article seeks to reposition voluntary redundancy as a key element of the raft of measures that changed the face of the British society.